Incorporation of spirobifluorene regioisomers in electron-donating molecular systems for organic solar cells. Issue 31 (9th March 2016) - Bulut, Ibrahim; Chávez, Patricia; Fall, Sadiara; Méry, Stéphane; Heinrich, Benoit; Rault-Berthelot, Joëlle; Poriel, Cyril; Lévêque, Patrick; Leclerc, Nicolas
Abstract : We report herein the synthesis and characterizations of new small molecules for organic photovoltaics including diketopyrrolopyrrole and spirobifluorene. Abstract : We report herein the synthesis and characterizations of new small molecules for organic photovoltaics including diketopyrrolopyrrole and spirobifluorene. Two grafting positions of the spirobifluorene units are used leading to two regioisomers with different optoelectronic properties. Despite, the moderate photovoltaic performances, we show that the incorporation of spirobifluorene as a three-dimension platform into conjugated material backbones allows the increase of dimensionality and brings a more isotropic character to the charge transport properties of the final materials. The solubility is also increased despite the low density of grafted alkyl side-chains, which is an important feature for the future of this technology.